Data-driven small-signal stability assessment of power systems - Wang, Xurui (Nanyang Technological University, 2021)
The widespread usage of renewable energy sources such as solar and wind power shows that mankind is building a green and low-carbon energy consumption system. Due to the intermittent nature of renewable energy sources (RES), the stability of the system is facing more serious challenges as increasing integration of RESs to the modern power systems. The assumption that the system's operational point state will not change over relatively long time period is required for the use of traditional stability analysis methodologies. However, because intermittent renewable energy sources result in an ever-changing power flow pattern, conventional approaches are ineffective for evaluating system stability.